Development of Nursing Professional Readiness Perception Scale - Merve Tarhan; Aytolan Yıldırım (Association of Nurse Managers, 2021)
INTRODUCTION: The study was conducted to develop a valid and reliable measurement tool for determining perceptions of senior nursing students about their professional readiness. METHODS: The methodological study was conducted between January-March 2018 with 362 senior nursing students studying in nursing departments of two universities in Istanbul. The item pool of the scale was created based on the relevant literature data. Personal Information Form and Nursing Professional Readiness Perception Scale were used to collect data. The data were evaluated by descriptive statistics, explanatory and confirmatory factor analysis, Pearson correlation analysis, t-test in dependent groups and Cronbach alpha coefficient. RESULTS: As a result of feasibility factor analysis, item analysis, explanatory and confirmatory factor analysis, 38 items were removed from the scale. Goodness of fit statistics with 15 items and three subdimensions were found to be acceptable/excellent. Cronbach alpha coefficient was determined as.90. Although statistically significant difference was not detected between the test and retest mean scores (p>.05) and a significant positive correlation was detected between them (r=.87; p<.001). DISCUSSION AND CONCLUSION: It was concluded that the scale is a valid and reliable tool and can be used to determine the professional readiness perceptions of senior nursing students.